2017
DOI: 10.3390/rs9121338
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Impacts of the Air Temperature on Greening and Senescence in Alaskan Arctic Plant Tundra Habitats

Abstract: Climate change is warming the temperatures and lengthening the Arctic growing season with potentially important effects on plant phenology. The ability of plant species to acclimate to changing climatic conditions will dictate the level to which their spatial coverage and habitat-type dominance is different in the future. While the effect of changes in temperature on phenology and species composition have been observed at the plot and at the regional scale, a systematic assessment at medium spatial scales usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 47 publications
5
18
0
Order By: Relevance
“…This is supported by May et al. (), who found that warmer temperatures slowed, and cooler temperatures increased, the rate‐of‐senescence at short time scales (3 d). Despite warming air temperature, and soil temperature to a lesser extent, we did not observe slower rates of senescence in response to warming.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…This is supported by May et al. (), who found that warmer temperatures slowed, and cooler temperatures increased, the rate‐of‐senescence at short time scales (3 d). Despite warming air temperature, and soil temperature to a lesser extent, we did not observe slower rates of senescence in response to warming.…”
Section: Discussionsupporting
confidence: 56%
“…Similarly, near‐surface measurement of NDVI using a mobile sensor platform found senescence occurred later with warmer August temperatures (May et al. ). Early senescence may occur in water‐limited systems when conditions are dry, such as in grasslands (Liu et al.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations